The Plasticity of Neutrophil Subsets in Inflammation - Ui Mhaonaigh, Aisling (Trinity College Dublin. School of Medicine. Discipline of Clinical Medicine, 2022)
Neutrophils are a vital component of the innate immune system and the body s first line of defense against invading pathogens. The classic view of these cells is that they are a homogenous population of terminally differentiated cells with clearly outlined functions. Recently evidence has revealed that neutrophils are a functionally versatile cell type and are responsible for both inflammation and immune response. Indeed, the role played by neutrophils in various disease conditions ranging from autoimmunity to bacterial and viral infections and cancer has led to a renewed interest in their roles in pathological inflammation. In this thesis I set about investigating the plasticity of neutrophils in inflammation using ANCA vasculitis and COVID-19 (COVID-19) as disease models. The presence of low-density neutrophils in a variety of diseases suggests a relationship between the underlying disease state and their production. ANCA vasculitis (AAV) is a systemic autoimmune disease in which neutrophils play a vital role. More recently there have been reports of LDGs in COVID-19 a systemic viral disease. I directly compared the frequency and phenotype of these cells in acute and remission AAV and in mild moderate and severe COVID-19. LDGs are elevated and linked to severity in both diseases. Immature neutrophils are elevated in both conditions, likely due to extreme left shift from emergency granulopoiesis. These results suggest that LDGs are a generic response to inflammation and not a result of disease specific triggers. To establish an immunomodulatory role for neutrophils, I focused on arginase 1, an enzyme linked to T cell suppression. Interestingly, normal density granulocytes (NDGs) in severe COVID-19 had significantly lower arginase levels than their AAV counterparts and healthy controls (HC). Imaging flow cytometry confirmed dysfunctional arginase distribution within the cell. These differences may be severity related. I also investigated the levels of arginase 1 protein and enzyme activity in serum from COVID-19 patients, paradoxically these were lower than HCs suggested that arginase 1 may have been already exocytosed or that an aberrant release mechanism was at play. Neutrophils from COVID-19 patients failed to suppress T cell proliferation in vitro. Having established that it was NDGs not LDGs that display disease-specific differences, and to reduce handling and user bias, I focused on the identification of neutrophil subsets in whole blood. Using traditional and imaging flow cytometry I identified higher levels of immature neutrophils and activated subsets in COVID-19 than AAV. I identified a population of CD33+ cells in convalescent COVID-19 that was not present in HC. This population was confirmed by high-dimensional analysis using UMAP and clustering algorithms to identify novel subsets. This subset is of particular note because it is present in an otherwise healthy individual and not in response to inflammatory conditions. Taken together, this data suggest that neutrophils respond to inflammation by both emergency granulopoiesis and degranulation leading to low density cells. The response is remarkably similar in both AAV and COVID-19, however the identification of a subset in convalescence not present in HC suggests that this neutrophil subset may be a bona fide subset and warrants further investigation.
APPROVED
Keywords: Neutrophils; ANCA Vasculitis; COVID-19